Reforming the education of economists in Europe: Breaking the tyranny of the top five - Henrekson, Magnus; Jonung, Lars; Lundahl, Mats (voxeu.org, 2025)
Many European countries have adopted the American model of doctoral training and academic evaluation. While this model suits America’s vast, mobile labour market, in Europe it has created perverse incentives and distorted research priorities. This column argues that Europe needs a more pluralistic, socially grounded, and inclusive system for the training of economists. It proposes a two-track approach for PhD training and evaluation that balances both frontier research and applied economics and policy. Europe should also consider broader evaluation and promotion criteria, more diversified PhD programmes, invest in policy-oriented research institutes, and promote the social relevance of the discipline.